Comparative Study of the Effects of Tai Chi and Square Dance on Immune Function, Physical Health, and Life Satisfaction in Urban Empty-Nest Older Adults - Su, ZhongJun; Zhao, JieXiu (Frontiers in Physiology, 2021)
Objective: To compare the effects of Tai Chi and Square dance on immune function, physical health, and life satisfaction in urban, empty-nest older adults. Methods: This cross-sectional study included 249 older adults (60–69 years) who were categorized into Tai Chi (n = 81), Square dance (n = 90), and control groups (n = 78). We evaluated immunoglobulin G (IgG) and interleukin-2 (IL-2) levels by enzyme-linked immunosorbent assay (ELISA), natural killer (NK) cell cytotoxicity by MTT assay, physical health indices by physical fitness levels, and life satisfaction by Life Satisfaction Index A (LSIA) scores. Results: Immune function, physical health, and life satisfaction in older adults in the Tai Chi and Square dance groups were significantly better than those in the control group (P < 0.05). Regarding immune function and physical health, the Tai Chi group exhibited significantly higher levels of IgG (15.41 ± 0.26 g/L vs. 11.99 ± 0.35 g/L, P < 0.05), IL-2 (4.60 ± 0.20 ng/mL vs. 4.45 ± 0.21 ng/mL, P < 0.05), and NK cell cytotoxicity (0.28 ± 0.02 vs. 0.22 ± 0.02, P < 0.05) than the square dance group, significantly lower waist-to-hip ratio (0.87 ± 0.02 vs. 0.89 ± 0.02, P < 0.05), resting pulse (78.4 ± 4.6 beats/min vs. 81.0 ± 3.1 beats/min, P < 0.05), systolic blood pressure (132.0 ± 5.2 mmHg vs. 136.2 ± 3.2 mmHg, P < 0.05), diastolic blood pressure (80.0 ± 2.6 mmHg vs. 83.0 ± 2.7 mmHg, P < 0.05), and significantly higher vital capacity (2978.0 ± 263.0 mL vs. 2628.3 ± 262.8 mL, P < 0.05) and duration of one-leg standing with eyes closed (16.2 ± 1.9 s vs. 12.0 ± 1.7 s). However, there was no significant difference in LSIA scores between the Tai Chi and Square dance groups (12.05 ± 1.96 vs. 13.07 ± 1.51, P > 0.05). Further, there was a significant correlation between LSIA scores and immune function (r = 0.50, P = 0.00) and physical health (r = 0.64, P = 0.00). Conclusion: (1) Both Tai Chi and square dance practitioners had better health outcomes, compared with sedentary individuals; (2) Tai Chi practitioners had better physical health and immune function than Square dance practitioners. (3) Tai Chi and Square dance exercises had similar effects on life satisfaction among urban empty-nest older adults. Suggestions: For urban empty-nest older adults who want to have better physical health and immune function, long-term Tai Chi exercise may be a better choice; however, those who are concerned about life satisfaction can choose either Tai Chi or Square dance exercise.